Knowledge and Attitude towards Patient Safety among a Group of Undergraduate Medical Students in Saudi Arabia - Almaramhy, Hamdi; Al-Shobaili, Hani; El-Hadary, Kamal; Dandash, Khadiga (International Journal of Health Sciences, 2011)
Objectives: This study aimed to measure knowledge and attitude of undergraduate medical students towards patient safety concepts, and to detect variation by the mode of learning. Methodology: A cross sectional study administrated an anonymous questionnaire to a random sample of 150 medical students graduated from two national medical schools, one follow the traditional lecture based learning (LBL) and the other applies innovative learning strategy (ILS). Students’ self-ratings of knowledge level and attitude towards patient safety in relation to the mode of learning were measured. The study was conducted in April 2010. Results: More than half of the participants (52.7%) self- rated their general knowledge on patient safety on good level compared to 27.3% for the specific knowledge issues score. Most participants (60.7%) agreed the importance of patient safety. The majority agreed to support peers who make unintentional errors and not to blame them for their own mistake (76.0 and 80.7% respectively). Less than half (44.7%) of the participants agreed the patients’ role in error prevention and 47.3% agreed error disclosure to the patient. ILS participants were significantly more recognizable of the patient safety issues: problem solving (P< 0.01 OR: 3.0) and error management (P< 0.001 OR: 2.4) than the ILS colleagues. Conclusion: The study revealed unsatisfied percentages of the participants who self- rated ‘good’ for their general and specific knowledge on patient safety. The unsatisfied rate was reported for the participants’ ‘agree’ score towards patient safety issues. Basic relevant educational interventions with focus on deficient issues are recommended. Key words: Patient safety, Medical errors, Medical students, Saudi Arabia